Enhancing anticipation control of the posture system in the elderly wearing stroboscopic glasses - Yi-Ching Chen; Yi-Ying Tsai; Yen-Ting Lin; Ing-Shiou Hwang (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Stroboscopic vision (SV), known for providing intermittent visual input, has been recently integrated into postural training to improve proprioceptive awareness. This research examined the impact of SV on cortico-posture coupling in older adults, along with the related changes in postural control throughout a spectrum of feedback and feedforward processes. Methods A total of thirty-three adults, averaging 66.1 ± 2.5 years of age, were tasked with maintaining an upright posture on a stabilometer, utilizing either complete or intermittent visual guidance. Stabilogram diffusion analysis (SDA) was employed to assess balance strategies based on postural sway, while phase-amplitude coupling (PAC) between postural fluctuations and scalp EEG provided insights into the associated neural control mechanisms. Results SV resulted in significantly increased postural sway as compared with that of full-vision feedback (p < 0.001). SDA results indicated greater critical point displacement (CD) (p < 0.001), short-term diffusion coefficients (Ds) (p < 0.001), and scaling exponents (Hs) (p = 0.014) under SV conditions. PAC analysis revealed that the coupling between the postural fluctuation phase and cortical oscillation amplitude in the theta and alpha bands of the fronto-central area was significantly greater in the SV condition than in the full-vision condition (p < 0.001). Additionally, SV led to increased beta PAC in the frontal and sensorimotor areas compared to that of full vision (p < 0.001), which negatively correlated to SV-dependent changes in open-loop gain (Hs) (p < 0.05). Conclusions SV transitions postural sway towards an open-loop process and influences cortico-posture interactions in older adults, emphasizing a neuromotor adaptation to the uncertainty in feedforward predictions when utilizing intermittent visual feedback.